Teleworking and Psychological Well-being: Insights and Applications for TVET - Mohd Lokman, Anitawati; Zainal, Natasha; Hamidi, Saidatul Rahah; Ana Hadiana (Journal of Technical Education and Training, 2024)
The shift to teleworking has reshaped the work environment, introducing new dynamics and challenges. This transition is particularly relevant in the context of Technical and Vocational Education and Training (TVET), where preparing students for the evolving job market is essential. This study addresses the limited scientific analysis of how teleworking affects psychological well-being. Understanding these impacts is crucial for TVET institutions to equip students with the skills needed to thrive in remote working environments. The objectives are to identify the determinants of psychological well-being related to teleworking, analyze their impact, and propose a conceptual model linking these determinants to well-being. This study aims to fill the gap in existing research by providing concrete evidence and insights. The methodology involves a quantitative approach, using a survey questionnaire administered to 107 participants from a selected area. Data collection focuses on various factors influencing psychological well-being, and the analysis employs statistical methods to identify significant determinants and their relationships. The findings reveal key determinants of psychological well-being in teleworking, such as resilience, time management, and technology proficiency. These determinants are synthesized into a conceptual model that highlights their impacts and interconnections. The study’s significance extends to TVET institutions by enhancing support services, providing mental health resources and counseling, establishing mentorship programs, and fostering partnerships with employers. These initiatives aim to better prepare students for teleworking, contributing to a healthier, more resilient workforce.